Corona Discharge Detection Analysis on Aluminum and Iron Conductors by Point Field Electrode Method - Nugroho, Satrio Dwi; Setiabudy, Rudy; Negara, Roy Bayu; Aliffianti Ulfiah, Shindy; Azhary Arsal, Fanji (International Journal of Engineering, Science and Information Technology, 2025)
Currently, Southeast Asia's highest primary energy usage is in Indonesia. Electrical infrastructure like transmission and distribution will be directly responsible for the high energy use. More distribution electrical networks will be in place due to the growing demand for electricity. So, the more significant the electrical disruptions that arise. Corona is one type of electrical disruption in the medium voltage network system. Corona is caused by a partial release of electrical charge, meaning the charge does not entirely pass through both conductors. The surrounding air experiences dielectric stress, producing noise, purple light, and a characteristic smell. Corona's appearance may seriously affect electrical equipment. Additionally, there are other ways to identify the appearance of corona, including using the senses of sight, smell, and hearing. The hearing approach involves utilizing a sound-capable sensor to detect corona. By taking pictures of the location of the corona, one can use sight to detect it. On the other hand, an ozone gas sensor is used in the scent approach. The author attempted to use the method of scent in this investigation. An ozone sensor will record corona disruptions that occur at the delivery site. Oxygen can be broken down into ozone because the air around the corona may ionize the surrounding air.